Advancements in Surface Modification Techniques by Metal Fluoride Coating for Enhanced Electrochemical Performance of Cathode Active Materials in Li‐Ion Batteries - Merve Gençtürk; Ahmet Aksöz; Kamil Burak Dermenci; Emre Biçer (ChemElectroChem)
The demand for high‐performance Li‐ion batteries spans diverse applications from portable electronics to electric vehicles and smart grid systems. Li‐ion batteries face challenges in fast charging/discharging, high capacity, and rate capability due to their microparticle scale active materials. Researchers are addressing these limitations by exploring nanoscale materials and surface modifications, particularly focusing on cathode enhancements. Lithium‐rich layered oxide compounds, with theoretical capacities exceeding 200 mAh g−1, show promise in overcoming capacity constraints. However, issues like low Coulombic efficiency and weak rate capability persist, necessitating innovative solutions. Surface modification techniques using inert or active materials have potential in improving electrochemical properties by preventing direct active material–electrolyte interaction, thus reducing capacity degradation. Coatings with materials, like AlF3, MgF2, CeF3, and so on, have demonstrated significant battery performance enhancements. Metal fluoride coatings provide stability and facilitate faster Li‐ion intercalation/deintercalation, leading to improved cycle stability and rate capability. Ongoing research aims to understand reaction mechanisms during initial charging, with in situ studies exploring crystal structure changes. Successful surface modification examples include coating lithium‐rich layered materials with metal fluoride, resulting in increased discharge capacity and reduced polarization, indicating enhanced Li‐ion intercalation/deintercalation.